Evaluation of the effectiveness of the DASH diet in hypertensive patients (Research, Society and Development, 2022)
Objective: To evaluate the efficacy of the DASH diet in hypertensive patients in a municipality in southern Minas Gerais, Brazil. Methodology: Prospective longitudinal study, performed with thirteen hypertensive subjects, mean age of 62.5 ± 10.5 years, recruited from the Physical Therapy Clinic of the city of Alfenas, Minas Gerais. Individual and group visits were performed. Individual evaluation occurred at time 0 (baseline), 7th day and 37th after first evaluation. Group activities were performed on the 15th and 30th days after first evaluation. Changes in nutritional status (anthropometric and body composition), dietary pattern (total DASH diet score) and BP were considered as outcomes. Results and discussion: No statistical differences were found in nutritional status, dietary pattern and BP (p> 0.05). However, it was found that subjects reduced on average 1.01 ± 2.3 kg of body weight after 37th day of intervention (p=0.07). High adherence of intervention was observed, regarding to DASH diet, in 61.5% patients (n = 6). Conclusion: Even with a short intervention time (30 days), positive results were observed regarding dietary pattern of some of DASH diet components and a tendency to reduce body weight.